COMBATING ORGANIZED CRIME IN UKRAINE: CURRENT PROBLEMS AND POSSIBLE SOLUTIONS - Shamara, Oleksandr; Komashko, Volodymyr (Стратегічна панорама, 2024)
This article presents the findings of a state-of-the-art analysis of Ukrainian legislation in the field of combating organized crime. The authors focus on specific features of meeting Ukraine’s obligations under the United Nations Convention against Transnational Organized Crime, as well as implementing the provisions of the National Security Strategy of Ukraine (2020), the Strategy of Safeguarding State Security (2022) and the Strategy for Combating Organized Crime (2020). The special services of some foreign states continue intelligence and subversive activities against Ukraine, try to feed separatist sentiments, and use organized criminal groups and corrupt officials to strengthen their influence. In this context, the authors emphasize the need to safeguard state security by intensifying the fight against terrorism and organized crime, and counteracting the erosion of the state apparatus and local self-government bodies, which occurs due to the spread of systemic corruption in state bodies. The authors conclude that Ukraine lacks a systematic approach to combating organized crime, which is manifested through an inadequate level of interaction among law enforcement agencies in the relevant fields, an outdated and unbalanced regulatory framework for combating organized crime, an imperfect procedure for monitoring the criminogenic situation, a lack of a consolidated objective methodology for assessing threats from organized crime, and a reliance on obsolete forms and methods of combat. These factors aggravate problems related to organized crime and the low level of effectiveness of the fight against it. There is a need to consider the establishment of special bodies combating organized crime and the division of the fight against organized crime into strategic and tactical levels. The authors propose to entrust the fight against organized crime at the strategic level to a special-purpose state body with law enforcement functions.